PENGARUH PENGGUNAAN DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADAPT PEGADAIAN (PERSERO) KANTOR CABANG DENPASAR - Ni Komang Pebi Arisanti; Gede Juliarsa (BORJUIS: JURNAL OF ECONOMY, 2025)
The development of information technology has led to a shift in the use of manual information systems to computer-based information systems that allow various activities to be carried out more quickly, precisely, and accurately. The purpose of this study is to empirically prove the influence of the use and utilization of information technology on the eflectiveness of accounting information systems. This research was conducted at PT Pegadaian (Persero) Denpasar Branch Office. This study uses a quantitative approach with multiple linear regression analysis techniques. The population in this study was 74 people, with a nonprobability sampling method, namely by purposive sampling technique, so that a sample of 55 samples was obtained. The results of this study indicate that the influence of the use and utilization of information technology has a positive eflect on the eflectiveness of accounting information systems. The coefficient of determination (Adjusted R Square) obtained was 0.708, meaning that a percentage of 70.8% of the eflectiveness variable of the accounting information system can be explained by the variable of the influence of the use and utilization of information technology, while the remaining 29.2% is explained by other variables that were not studied. The implications of the results of this study are able to provide suggestions or input for pawnshops, especially PT Pegadaian (Persero) Denpasar Information Branch Office, in an eflort to improve the eflectiveness of the accounting system by paying attention to the use of information technology in carrying out its operational activities, and increasing the use of good information technology for the company.